Attitudes of Jordanians People toward Marriage for Persons with Sensory Disabilities, and the effect of some variables on it (Descriptive and Comparative Study) - K. AlTarawneh, Rodaina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed to know the attitudes of Jordanians people toward marriage for persons with sensory disabilities (visual or hearing impairment). And it aimed to Investigated the effect of some variables on these attitudes. In order to achieve the aims of this study, a scale of attitudes toward marriage for persons with sensory disabilities were used to collect data from (800) persons. The results indicated that the percentage of Jordanians people who supported marriage for persons with sensory disabilities was (82.1). Also it indicated that there are statistically significant differences between the Jordanians people in the attitudes toward marriage for persons with sensory disabilities due to Gender and Age. Also there are no statistically significant differences between Jordanians people in the attitudes due to Educational level and Existence of a disability in the individual’s family).